Pattern of Problem Solving in Religious Harmony Forum - Syam, Nur; Basyid, Abdul (Millati: Journal of Islamic Studies and Humanities, 2024)
This article aims to deepen the patterns of conflict resolution over religious issues in the Religious Harmony Forum (FKUB) in three different provinces, namely North Sumatra, West Java, and East Java. In addition, to recognize the value and role of collegial collective leadership in solving inter-religious problems in each province. This research chose a qualitative approach with descriptive methods. The data revealed is in the form of verbal expressions from the subjects or key informants and informants and then recorded and written according to the categories that have been determined. A multisite design was used in this research because the study focused on FKUB’s collegial collective leadership in resolving inter- or internal life problems among religious communities. The result of this study disputes between religious communities and the construction of houses of worship are two issues that are often assisted by FKUB in their resolution. Negotiations between religious adherents are used to seek answers to problems in the context of conflict resolution based on local wisdom, inclusive diversity, upholding mutual respect and equality, and are open to accepting ideas and views, from different points of view.